Performance and metabolomic urinalysis of heat-stressed dairy goat fed diet supplemented with soybean oil - Md Nayan, Mohd Nazri (2014)
Heat stress negatively affects the animal production that could result in devastating economic lossess. The benefits of supplementing dietary fats to the animals under such conditions have been extensively reviewed. However, there is a lack of information on the effects of soybean oil supplementation on the performance of the animals, particularly under heat stress conditions. In addition, the application of the state-of-the-art technology such as 1H NMR-based metabolomics to study the fundamental physiological processes in animal production study is still few. The first experiment was carried out to assess the productive performance, thermoregulatory functions and milk parameters of heat stressed Murciano-Granadina goats fed diets supplemented with soybean oil. Meanwhile, the second experiment was conducted to identify possible metabolite markers as a result of the heat stress and soybean oil supplementation. The results from the first experiment showed that the heat stressed goats lost an average of 3.14 ± 2.30 kg of their body weight compared to the thermoneutral group that gained an average of 3.19 ± 2.62 kg of body weight. They also had a 39.1% lower dry matter intake (DMI), consumed 46.8% more water and produce 9.7% less milk compared to the thermoneutral group goats. Under heat stress conditions, there were significant correlations between temperature humidity index (THI) values and the water consumption (r = 0.66; P<0.01), rectal temperature (r = 0.94; P<0.001) and respiratory rate (r = 0.87; P<0.001). There were also nonsignificant (P>0.05) negative correlations between THI and DMI (r = -0.19) and milk production (r = -0.36). No significant effect (P>0.05) of soybean oil supplementation and its interaction with thermal conditions were found in any productive performance. Nonetheless, milk from supplemented animals were 23.2 and 1.6% higher in milk fat and protein content, respectively, besides 18.1 and 14.0% higher feed efficiency under heat stress and thermoneutral conditions,respectively. In the second experiment, partial least square – discriminant analysis (PLS-DA) model was only found significant (P<0.01) for heat stress vs.thermoneutral treatment groups comparison. Several metabolites of importance were identified which involved in various physiological response of animals to heat stress,such as increased harmful gut microbiota activity (hippurate), increased catecholamines and neurotransmitter activities (L-phenylalanine, glycine) and decreased degradation of energy-related metabolites (acetate, isoleucine and glutamate). The urine sample of the heat stressed goats was also shown to have a higher 3-hydroxybutyrate and lower creatinine, which are important in assessing the energy status of the animals. Despite the lack statistical evidence, soybean oil supplementation was shown to have beneficial physiologic effects on the animals,especially during heat stress with the higher creatinine level, and lower isoleucine and glutamate found in the urine. The present study has proved the adverse effects of heat stress on animal production. There was also economic and physiologic benefit of soybean oil supplementation despite no significant result on the productive performance was observed. Meanwhile, metabolite assessment provides a deeper understanding on the physiological response of the animals towards environment and feeding interventions.